Micro-plastics in soil environment: A review - Khan, M R; Tarafder, M A; Priti, M S; Haque, M A (Bangladesh Journal of Nuclear Agriculture, 2024)
Environmental scientists and other stakeholders have paid serious attention to soil pollution by microplastics in the last ten years. In soils, the microplastic particles act as a vector for the toxic persistent organic pollutants and potentially toxic metals that are easily sorbed by plants and enter the food chain. Microplastics are emerging as persistent terrestrial pollutants due to mismanagement and indiscriminate use. Microplastic contaminants affect the physicochemical characteristics of the soil as well as the feeding patterns of the soil biota. Sewage sludge, bio waste compost additions, plastic mulching, wastewater irrigation, landfill leachate, and air deposition are the causes of microplastics in soils. The amount of microplastics particles per kilogram of soil ranged from zero to thirteen thousand pieces. There are 523 times as many microplastic particles in the soil as there are in the ocean. Plant growth and seed germination are slowed down by the microplastic in the soil. Microplastics also affect the soil's enzymatic activities. The environmental sources of microplastic include plastic pellets, city dust, abrasion of road markings, tires, synthetic textiles, personal care products, and cosmetics. Human consumption through food can have a variety of harmful effects, including cytotoxicity, immunotoxicity, pulmonary toxicity, and reproductive toxicity. The current study describes the origins, distribution, and effects of microplastics on plants, soil biota, and human health in the soil environment. Bangladesh J. Nuclear Agric, 38(1): 1-19, 2024